2015
DOI: 10.1021/acs.langmuir.5b02077
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features of Micelles of Zwitterionic Dodecyl-phosphocholine (C12PC) Surfactants Studied by Small-Angle Neutron Scattering

Abstract: Small-angle neutron scattering (SANS) was used to investigate the size and shape of zwitterionic dodecyl phosphocholine (C12PC) micelles formed at various concentrations above its critical micelle concentration (CMC = 0.91 mM). The predominant spherical shape of micelles is revealed by SANS while the average micellar size was found to be broadly consistent with the hydrodynamic diameters determined by dynamic light scattering (DLS). Cryogenic tunneling electron microscopy (cryo-TEM) shows a uniform distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(72 citation statements)
references
References 41 publications
4
67
0
1
Order By: Relevance
“…This has been observed in several cryo-EM studies of membrane protein/detergent micelle complexes, and presumably results from some local organization of the detergent polar head-groups due to the high curvature of the micelle. It is likely that water molecules intercalate into this region of the micelle and account for the lower density areas in the lattice (18).…”
Section: Detergent (Ddm) Micelle (Turquoise Density): This Portion Ofmentioning
confidence: 99%
“…This has been observed in several cryo-EM studies of membrane protein/detergent micelle complexes, and presumably results from some local organization of the detergent polar head-groups due to the high curvature of the micelle. It is likely that water molecules intercalate into this region of the micelle and account for the lower density areas in the lattice (18).…”
Section: Detergent (Ddm) Micelle (Turquoise Density): This Portion Ofmentioning
confidence: 99%
“…Micelle-forming detergents provide amphipathic environments similar to those found in lipid bilayers and biomembranes. Micelles have different shapes and sizes determined by the chemical nature of their headgroups and the length of their hydrophobic tails (23,24). Physicochemical conditions such as temperature, solutes, and concentration can also affect micellar structure and eventually influence the conformation of bound proteins or peptides, especially the latter.…”
Section: Introductionmentioning
confidence: 99%
“…Our study focuses on TRP3 accommodation at the hydrophilic/ hydrophobic interface of micelles and subsequent events. The structure and dynamics of TRP3 were examined in the presence of micelles of different chemical nature: zwitterionic (lysolauroylphosphatidylcholine 1-lauroyl-2-hydroxy-sn-glycero-3-phosphocholine (LLPC), n-dodecylphosphocholine (DPC), and N-dodecyl-N,N-(dimethylammonio) butyrate (DDMAB), anionic 1-myristoyl-2-hydroxy-sn-glycero-3-phospho-(1 0 -rac-glycerol) (LMPG), and nonionic (octylglucoside (OG)) (23,24,(31)(32)(33)(34)(35). The conformational ensemble was evaluated during detergent titration and it was found that the peptide interacts via conformational selection.…”
Section: Introductionmentioning
confidence: 99%
“…[f ]The numerical values must be considered with caution since the ISE traces showed an initial efflux that was not maintained during the experimenttime (see Figures S58-60 in the SupportingInformation). DPC micelles, [16] and much larger than the r H of the cage when DOSY NMR spectroscopy was performed with 1c in [D 6 ]DMSO (0.66 nm alone and 0.76 nm with protonated 1c and TBACl). Theobserved changes in the NMR spectra of 1c within the micelles upon variations in the composition of the external aqueous solution were also very illustrative.T he proton NMR spectrum of the sample at pH 7.1 showed the presence of two sets of signals for some of the protons,which were especially important for those of the aromatic side chains (Figure 3).…”
mentioning
confidence: 99%